Kepastian Hukum Transaksi Dengan Menggunakan Mata Uang Dinar Dan Dirham Dalam Pendekatan Hukum Pidana Di Indonesia - Anwar, Faisal; Sriwidodo, Joko; Hutomo, Putra (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
Legal certainty related to transactions using Dinar and Dirham currencies in the criminal law approach in Indonesia. Based on Law No. 7 of 2011 on currency, Rupiah is the only legal tender in Indonesia. The use of currencies other than Rupiah, including dinars and dirhams, is not legally recognized and has the potential to violate criminal provisions, such as those related to fraud or forgery. However, this phenomenon also involves social and cultural dimensions, especially in communities based on sharia economics, where dinars and dirhams are considered as means of transaction that are more in line with Islamic principles of justice and ethics. Overly repressive law enforcement can generate resistance in society, so more inclusive legal reforms and adjustments are needed. By promoting dialogue and collaboration between policy makers, business actors, and the community, it is expected to create a legal system that is fair and responsive to social needs and is able to maintain legal stability in Indonesia . From the research results, the transfer of receivables by Cessie by the creditor in the event that the debtor fails to pay the third party mortgage guarantee does not comply with the applicable provisions as regulated in Article 613 of the Civil Code and Law of the Republic of Indonesia Number 4 of 1996 concerning Mortgage Rights. Form legal protection for third parties by filing a lawsuit before or during the execution process. The government, stakeholders and related parties are expected to make changes to Law of the Republic of Indonesia Number 4 of 1996 concerning Mortgage Rights over Land and Objects related to Land, by accommodating third party protection which is explicitly regulated in guaranteeing rights to land, these regulations do not clearly regulate the rights and obligations of third parties so they cannot provide legal protection for collateral owners. The results of this study that legal certainty related to transactions using dinars and dirhams, as done by Zaim Saidi, in the approach of Indonesian criminal law is a violation of Article 9 of Law No. 1 of 1946 on Criminal Law regulations in conjunction with Law No. 7 of 2011 on currency. Enforcement of these transactions can be carried out through the application of criminal sanctions, since the use of currencies other than Rupiah for payment purposes is not justified by law. In addition, the low legal awareness of the public in using the Rupiah as a legal tender also became an important factor in this case.